Prevalence of Temporomandibular Disorder Symptoms, Oral Behaviors and Depressive Symptoms in the University of the Philippines Manila College of Dentistry Community/ Rossa Ynez B. Cabrera. - Cabrera, Rossa Ynez B.
INTRODUCTION: Temporomandibular disorders (TMD) are considered a public health concern. This study determined the prevalence of TMD symptoms, oral behaviors, and depressive symptoms in a public university, a microcosm of the Filipino population, following the biopsychosocial model.